Occurrence and growth characters of Amanita spp. In Garhwal Himalaya - and R.C. UPADHYAY, K.C. SEMWAL*, R.P. BHATT (Indian Phytopathology, 2006)
An attempt has been made to correlate the growth and development of fructifications of eight Amanita spp. in nature with temperature and rainfall in three different forests types of Garhwal Himalaya. Average stipe elongation, pileus diameter and life span varied with temperature and moisture and recorded more in the early season (mid- June to Aug.) than the late season (Sep. to mid- Oct.). The studies have indicated that the life span of a particular species is inversely proportional to the daily growth of Amanita spp.